DETERMINANTS OF CLASSROOM SEATING ARRANGEMENT IN HIGHER EDUCATION INSTITUTIONS - G. SHAINY*, T. NEERAJA; V. PRASUNA (The Journal of Research ANGRAU, 2020)
The study was to assess and evaluate the determinants of classroom seating arrangement in higher education institutions in Guntur district of Andhra Pradesh. Thirty higher educational institutes (30 respondents) were selected for the study. Eleven design features that guide the seating arrangement in a classroom proposed by various higher educational institutes and official bodies served as a base for identifying the features to evaluate the seating arrangement in a classroom. The results showed that educational institutes were not paying attention to the modified fan-shaped design configuration, theatre-style seating, and seating arrangement for students with disabilities. The total strength of the students and year of establishment of the institution were the deciding factors in designing a seating arrangement in a class, row to row clearances, passage clearances, minimum and maximum distance between the last row to end wall, clearances from the student’s desk adjacent wall, desk to desk clearances, seating for students with a disability and seating design configuration.